1998
DOI: 10.1037/0012-1649.34.3.540
|View full text |Cite
|
Sign up to set email alerts
|

Maternal drug use during pregnancy: Are preterm and full-term infants affected differently?

Abstract: This study examined whether preterm infants are more vulnerable to the effects of prenatal drug exposure than are full-term infants. The sample of 235 low-income African American mothers and their infants included 119 cocaine-polydrug users, 19 alcohol-only users, and 97 nonusers; 148 infants were full term and 87 were preterm. Direct effects of exposure on birth weight, birth length, ponderal index, and irritability were moderated by length of gestation: Fetal growth deficits were more extreme in later-born i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
2
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 58 publications
0
74
2
2
Order By: Relevance
“…32 We found that decreasing or low tobacco use was the only pattern associated with greater birth weight, length, and head circumference, compared with decreasing patterns of use of other drugs. The clinical implications of this study are that illicit drug use as well as alcohol and tobacco use should be curtailed during pregnancy.…”
Section: Discussionmentioning
confidence: 87%
“…32 We found that decreasing or low tobacco use was the only pattern associated with greater birth weight, length, and head circumference, compared with decreasing patterns of use of other drugs. The clinical implications of this study are that illicit drug use as well as alcohol and tobacco use should be curtailed during pregnancy.…”
Section: Discussionmentioning
confidence: 87%
“…10,12 Brown et al 11 reported greater levels of irritability in preterm infants exposed to cocaine in utero. In our large cohort, we observed no relationship between the gestation and the development of NAS.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] Preterm infants may be less likely than term infants to exhibit signs of NAS resulting from opiate or opioid exposure. [10][11][12] There is conflicting evidence with regard to optimal maternal methadone dose in pregnancy, with some studies showing an association between maternal methadone dose and the risk of NAS and some studies showing no such relationship. 9,[13][14][15][16][17][18][19] Duration of stay may be longer for infants born to polydrug-misusing mothers, 20 and since higher doses of methadone have been associated with less polydrug use, reducing methadone during pregnancy may not be justified.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, one pathway explaining potential associations between cocaine exposure and infant reactivity and regulation may be via compromised fetal growth. Fetal growth may also moderate this association (Brown et al, 1998a). In other words, fetal growth may interact with exposure status such that cocaine-exposed infants with poor fetal growth such as lower birthweight (controlling for gestational age) may be at highest risk for poor autonomic regulation.…”
Section: Indirect Effects and Moderationmentioning
confidence: 99%